2009
DOI: 10.1021/pr900634c
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ Underestimation in Simple and Complex Mixtures: “The Good, the Bad and the Ugly”

Abstract: The increasing popularity of iTRAQ for quantitative proteomics applications makes it necessary to evaluate its relevance, accuracy, and precision for biological interpretation. Here, we have assessed (a) the accuracy and precision of iTRAQ quantification in a controlled experimental setup, using low- and high-complexity protein mixtures; and (b) the potential pitfalls that hamper the applicability and attainable dynamic range of iTRAQ: isotopic contamination, background interference, and signal-to-noise ratio.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
501
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 458 publications
(527 citation statements)
references
References 21 publications
23
501
3
Order By: Relevance
“…Mean log ratio (VSN1ϪVSN2) have problems with accuracy by systematically underestimating ratios (23)(24)(25)(26)(27). To assess this question, we prepared a sample with proteins at known ratios.…”
Section: Percentilementioning
confidence: 99%
See 3 more Smart Citations
“…Mean log ratio (VSN1ϪVSN2) have problems with accuracy by systematically underestimating ratios (23)(24)(25)(26)(27). To assess this question, we prepared a sample with proteins at known ratios.…”
Section: Percentilementioning
confidence: 99%
“…This effect was seen on both data collected with a QSTAR and with a QTof Premier, suggesting that the effect is ubiquitous and not dependent on the MS technology used. It has been suggested that this underestimation arises from contaminating peptides with similar m/z ratios during ion selection prior to collision-induced dissociation (23,27). A quantitative model reveals that when the relative amount of contamination is the same within an experiment a linear relationship between observed and true ratios is expected and would be independent of signal strength.…”
Section: Percentilementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that iTRAQ labeling is associated with bias; fold changes are compressed toward one (11)(12)(13)(14). It has been suggested that this underestimation of fold change is caused by co-eluting peptides with similar m/z values that are isolated together, creating mixed iTRAQ intensities in complex samples (14).…”
mentioning
confidence: 99%